Costa Rica : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Despite the oil price shock, growth has been high. Discussions focused on the policies needed to reduce Costa Rica's vulnerabilities, enhance growth, and reduce poverty in a lasting way. Passage of a substantial tax reform is essential. To bring inflation down to low single digits, the authorities plan to recapitalize the central bank and move gradually to a more flexible exchange rate regime. This Article IV Consultation provides an important opportunity to take stock of Costa Rica's achievements and the challenges ahead.